Edukasi Kesehatan Reproduksi dengan Risiko Pernikahan Usia Dini pada Remaja Usia 15-19 Tahun di Desa Bangun Rejo Kecamatan Tanjung Morawa Kabupaten Deli Serdang Provinsi Sumatera Utara Provinsi Sumatera Utara Tahun 2023 - Srininta Srininta; Mesrida Simarmata; Lisdayanti Simanjuntak; Perkasa Ginting; Desy Herawati Simanjuntak; Eldawati Sinaga (Jurnal Nusantara Berbakti, 2024)
Background: 30% of women are still married under 18 years. Law No. 1 of 1074 concerning marriage states that men and women can marry after the age of 19. The reasons why teenagers marry early are knowledge, education, economics, the role of peers and promiscuity. The impacts of early marriage include giving birth to low birth weight babies, abortion and others. Objective: Increase teenagers' knowledge about the risks of early marriage. Method: Providing Reproductive Health education to 30 teenagers aged 15-19 years in Bangun Rejo Village. Results: 15 people (50%) had good knowledge before the education was carried out, but after the education was carried out the knowledge and good knowledge was 24 people (80%) in the same group. Conclusion: There is an increase in adolescent knowledge after being given reproductive health education regarding the risks of early marriage in adolescents 15-18 years in Bangun Rejo Village.